2007
DOI: 10.1111/j.1439-0434.2007.01329.x
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Moderately Halophilic Bacteria to Control Grey Mould Disease on Tomato Fruits

Abstract: Tomato is one of the leading crops in Tunisia in terms of weight consumed (20 kg⁄per person⁄year). Preserving the quality of the fruit from field to consumer is essential to successful marketing. Grey mould rot induced by Botrytis cinerea is an important cause of postharvest loss depending on season and handling practices. We describe here the ability of halotolerant to moderately halophilic bacteria isolated from different Tunisian Sebkhas (hypersaline soils) to protect freshmarket tomato fruits from B. ciner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 68 publications
0
59
0
Order By: Relevance
“…Thus, agricultural industries need in novel biofungicide formulations (Gohel et al 2007). Chitinolytic enzymes, which are key players in the lysis of cell walls of higher fungi, are produced by several microorganisms including bacteria (Sadfi-Zouaoui et al 2008;Essghaier et al 2009). Recently, a number of commercial biocontrol products have been developed from rhizobacteria, and many plant disease biocontrol products that contain Bacillus spp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, agricultural industries need in novel biofungicide formulations (Gohel et al 2007). Chitinolytic enzymes, which are key players in the lysis of cell walls of higher fungi, are produced by several microorganisms including bacteria (Sadfi-Zouaoui et al 2008;Essghaier et al 2009). Recently, a number of commercial biocontrol products have been developed from rhizobacteria, and many plant disease biocontrol products that contain Bacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research also aimed to identify the mode of action of the most successful isolates as this information may help optimize their biocontrol efficiency in the field. Understanding the mechanisms involved in biological control may enable efficacy to be enhanced (Sadfi-Zouaoui et al 2008;Essghaier et al 2009). We reported previously the efficiency of the moderately halophilic Virgibacillus marismortui strain M3-23 in biological control, and its high production of chitinase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous laboratory studies showed the efficiency of halotolerant Bacillus isolates in the control of potato dry rot under storage conditions (Sadfi et al, 2001(Sadfi et al, , 2002. Recently, we described the ability of moderately halophilic bacteria isolated from shallow salt lakes in Tunisia to protect fresh-market tomatoes and strawberry fruits from B. cinerea under commercial standard conditions (Sadfi-Zouaoui et al, 2008a;Essghaier et al, 2009). To our knowledge, we were the pioneer to evaluate the ability of halophilic bacteria to protect plant diseases from pathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Finding a broad antifungal enzyme able to function under such environmental conditions is relevant for biocontrol purposes. Previously, we have reported the efficiency of the halotolerant B. subtilis strain J9 in biological control under postharvest conditions on strawberries and tomatoes (Sadfi-Zouaoui et al, 2008a;Essghaier et al, 2009) and on tomato stems under greenhouse conditions (Sadfi-Zouaoui et al, 2008b). The main objective of this work was to evaluate the biological activity of the halotolerant B. subtilis strain J9 on strawberry plants under field conditions.…”
Section: Introductionmentioning
confidence: 99%